Degradation particles derived from high-purity magnesium inhibit osteogenic differentiation through regulation of macrophage polarization. (10th March 2023) - Sun, Yu; Yu, Han; Peng, Hongzhou; Kang, Xinbao; Peng, Zhaoxiang; Dong, Xieping; Wang, Wenhui; Song, Yang; Zhang, Xiaonong
Highlights: The osteoimmunology effects of degradation particles (DPs) derived from Mg were investigated. DPs could affect the polarization state of macrophages, which further affected osteogenic differentiation. It is a rare study focused on the negative effects of degradation of Mg-based implants. Abstract: Magnesium (Mg) and its alloys have great potential as orthopedic implant candidates, which could release various bioactive substances during degradation. Degradation particles (DPs) are one of the degradation products, but the osteoimmunology effects are still unclear. In this study, the effect of DPs on the polarization of macrophages and their release of cytokines was investigated. The results verify that excessive generation of DPs from biodegradable Mg can induce macrophages to realize polarization of proinflammatory M1 phenotype. Moreover, macrophages secrete proinflammatory cytokines to inhibit the osteogenic differentiation of rat bone marrow stem cells (rBMSCs). This suggests that the effects of DPs should be considered when evaluating Mg-based implants. DPs continuously produced with the degradation of Mg-based implants may influence osseointegration. Graphical abstract: Image, graphical abstract